Moving from physician-centered care towards patient-centered care for Parkinson's disease patients - van der Eijk, Martijn; Nijhuis, Frouke A.P.; Faber, Marjan J.; Bloem, Bastiaan R. (Parkinsonism & related disorders, 2013)
Today's society is changing rapidly and individuals increasingly favor an active role in designing their own lives. Contemporary patients are no exception, but the present health care system–which is organized primarily from the provider's perspective–is not yet prepared for this development. Here, we argue that an alternative way to organize health care, namely more from the patient's perspective, may help to contain costs, while improving the quality, safety and access to care. This involves a redefinition of the patient–doctor relationship, such that patients are no longer regarded as passive objects, but rather as active subjects who work as partners with health care professionals to optimize health (‘participatory medicine’). The opportunities that come with such a collaborative and patient-centered care model are reviewed within the context of patients with Parkinson's disease. We also discuss societal and Parkinson-specific barriers that could impede implementation of this alternative care model to the management of Parkinson's disease and other chronic conditions.